The State of Knowledge of Harmful Algal Blooms of Margalefidinium polykrikoides (a.k.a. Cochlodinium polykrikoides) in Latin America - López-Cortés, David J.; Núñez Vázquez, Erick J.; Dorantes-Aranda, Juan J.; Band-Schmidt, Christine J.; Hernández-Sandoval, Francisco E.; Bustillos-Guzmán, José J.; Leyva-Valencia, Ignacio; Fernández-Herrera, Leyberth J. (Frontiers in Marine Science, 2019)
The marine dinoflagellate Margalefidinium polykrikoides (=Cochlodinium polykrikoides) is a harmful species that has affected aquaculture, fisheries and tourism activities. It produces reactive oxygen species (ROS), as well as hemolytic and neurotoxic-like substances, that have been associated with the mortality of marine organisms. It has a tropical and subtropical distribution, and has the capacity to form cysts. The economic impacts for aquaculture industries are high, and has affected mainly Asian countries. In Latin America no economical estimates of the impacts that this dinoflagellate has caused, have been performed. HABs formed by M. polykrikoides are more frequent in Mexico and Central America, impacting aquaculture and fisheries activities. Proliferations of this dinoflagellate in this region are related with winds, upwelling, convergence areas, local convection of seawater, and eutrophication of coastal areas by runoff from rainwater and dragging of coastal waters containing nitrogen and phosphorus compounds; as well as with the increase of agricultural and aquaculture activities. Laboratory studies have provided detailed information regarding the growth of strains from this region, as well as their harmful effects on fish and shrimp, and the role that the production of ROS and polyunsaturated fatty acids have in toxicity. It is also possible that M. polykrikoides has an ecological role in the regulation of blooms of other harmful algae. In this contribution, we review the history of harmful algal blooms (HABs) of M. polykrikoides in Latin America, and the research that has been conducted with this species.